Case Report : Bilateral dentigerous cysts in association with developing third molars and premolars in a non-syndromic 13-year-old: a 2-year follow-up [version 1; peer review: 2 approved] - Sami Alshehri; Osama Zakaria (F1000Research)
Background Dentigerous cysts are benign, non-inflammatory odontogenic cysts that form over unerupted or partially erupted teeth. They are the second most common type of odontogenic cysts and can cause various complications if left untreated. Methods We report a rare case of bilateral dentigerous cysts in the mandible of a 13-year-old boy. Radiographic examination revealed two cysts on each mandibular side, associated with developing third molars and unerupted permanent second premolars. Histopathological examination confirmed the diagnosis of dentigerous cysts. Results The patient underwent surgical enucleation of all cysts and extraction of unerupted teeth under general anesthesia. The postoperative course was uneventful, with no recurrence observed over a 2-year follow-up period. Conclusions Dentigerous cysts are rare in children and even rarer in bilateral presentation. Early diagnosis and treatment are essential to prevent potential complications such as infection, tooth displacement, jaw fracture, or malignant transformation. This case illustrates the importance of radiographic examination and histopathological confirmation in the management of dentigerous cysts.